Analisis Prediksi Kebangkrutan Perusahaan Dengan Menggunakan Metode Altman Z-Score Pada Pt. Telekomunikasi Indonesia Tbk - Aprilaningsih, Winda, Dra. Mabruroh, M.M (2015)
This study aims to know the prediction of insolvency in PT. Telecommunication Indonesia Tbk. The method of Altman Z-Score is used to see know big the 2011-2013 period bankruptcy prediction in PT. Telecommunication Indonesia Tbk. The data used in this study is secondary data in the from financial report PT. Telecommunication Indonesia Tbk 2011-2013. Data source based financial report PT. Telecommunication Indonesia Tbk that registered on The Indonesia Stock Exchange and website www.idx.co.id. The data analysis technique used is the predictive model of Altman Z-Score bankruptcy. Which it applies the five variables representing liquidity ratio X1, X2 and X3 profitability ratio and activity ratio X4 and X5. Formula Z-Score = 0,717X1 + 0,847X2 + 3,107X3 + 0,420X4 + 0,998X5. Within the Z criteria > 2,90 is categorized as a healthy company. Z criteria 1,23 to 2,90 is categorized in gray area. Z criteria < 1,23 is categorized as a potentially bankrupt company. From the result of research Z-Score analysis that hass been done in PT. Telecommunication Indonesia Tbk 2011-2013 period can be know that PT. Telecommunication Indonesia Tbk is gray area company. It can be seen from the Z-Score value in 2011-2013 between 1,23 to 2,90. In 2011 Z-Score value is 2,3721. In 2012 Z-Score value is 2,489 and in 2013 Z-score value is 2,440.